Several Parameters of Blanching and Drying Influencing to Quality of Dried Pumpkin - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Is one such plant that is frequently being used as food as well as traditional medicine for long days. It is a large climbing herb, annual or perennial, for use as vegetable as well as medicine. It contains several phytochemicals including alkaloids, flavanoids, phenols, carbohydrates, tannins, saponins, terpenoids and proteins.  The presence of these phytochemicals has been found to possess various medicinal functional functions which are essential in the management of various diverse ailments.  Pumpkin has gained a considerable attention in recent years for its nutritional and health promoting values. Drying is a relatively simple process in which water activity in food is reduced, minimizing or inhibiting the chemical and enzymatic reactions and microbial growth that are responsible for its deterioration. Therefore, objective of this study focused on the effect of blanching temperature and time; heat pump drying temperature and storage condition to β-caroten (mg/100), vitamin C (mg/100g), rehydration capacity (kg moisture/kg d.s.), sensory score of the dried pumpkin (Cucurbita spp.). Results showed that pumpkin (Cucurbita spp.) should be blanched in hot water 95oC at 10 seconds in the present of citric acid 4g/l and then beeing dried by heat pump dryer at 50oC until 12% moisture. Blanching is carried out to improve food quality by inactivating enzymes, reducing microorganisms and preserve the natural color when pumpkin after blanching is subjected to drying. The final dried pumpkin was shelf-stable for a period of 12 weeks at ambient temperature without any appreciable adverse changes in physico-chemical as well as sensory quality characteristics of the dried products.Keywords: Pumpkin, Blanching, Drying, β-caroten, Vitamin C, Rehydration capacity.